2014
DOI: 10.1002/ps.3720
|View full text |Cite
|
Sign up to set email alerts
|

Use of acoustics to deter bark beetles from entering tree material

Abstract: The reduction in bark beetle entry into logs using particular acoustic treatments indicates that sound could be used as a viable management tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…We administered the vibracoustic recordings to Petri dishes using 10 contact actuators (DAEX13CT‐4 13 mm 3 W 4 Ω sound exciters; Dayton Audio, Springboro, OH) connected to each acoustic player (Lepai LP‐269FS 4x45 W Mini Amplifier; Aflitto & Hofstetter, 2014). The contact actuator results in both a vibratory component within the Petri dish and an airborne auditory component emitted by the Petri dish itself.…”
Section: Methodsmentioning
confidence: 99%
“…We administered the vibracoustic recordings to Petri dishes using 10 contact actuators (DAEX13CT‐4 13 mm 3 W 4 Ω sound exciters; Dayton Audio, Springboro, OH) connected to each acoustic player (Lepai LP‐269FS 4x45 W Mini Amplifier; Aflitto & Hofstetter, 2014). The contact actuator results in both a vibratory component within the Petri dish and an airborne auditory component emitted by the Petri dish itself.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound technologies have been promoted as an effective means of minimizing pest organisms in ponds and lakes, but little is known about the effects of ultrasound on non-target organisms (fish, frog, dog etc.,) or ecosystem processes when implemented on a large scale in complex natural systems (Aflitto and Hofstetter, 2014;LaLiberte and Haber, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Infrasonic is characterized as the sound below 20 kHz, whereas ultrasonic sound is defined as the sound above 18.000 Hz. Ultrasonic devices are typically marketed to target arthropod (including spiders, scorpions and insect pests) and mammal pests, while devices targeting birds operate within our normal hearing range (Aflitto and Hofstetter, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Both females and males of various species of insects produce and react to micro-vibrations thought to be involved with mate attraction. Predominantly this behaviour has been studied in tree and plant parasitizing species including the American grapevine leafhopper Scaphoideus titanus (Mazzoni et al, 2009), the southern green stink bug Nezara viridula (de Groot et al, 2010), the Asian citrus psyllid Diaphorina citri (Rohde et al, 2013) and the southern pine beetle Dendroctonus frontalis (Aflitto & Hofstetter, 2014). Studies have shown conspecific vibration patterns such as those from competing males (Mazzoni et al, 2009;Rohde et al, 2013) or heterospecific patterns such as those from a predator (de Groot et al, 2010), can alter male behaviour resulting in reduced mating events.…”
Section: Alternative and Novel Targetsmentioning
confidence: 99%